Pancreatic cancer derived 3D organoids as a clinical tool to evaluate the treatment response - Shukla, Hem D; Dukic, Tijana; Roy, Sanjit; Bhandary, Binny; Gerry, Andrew; Poirier, Yannick; Lamichhane, Narottam; Molitoris, Jason; Carrier, France; Banerjee, Aditi; Regine, William F.; Polf, Jerimy C. (Frontiers in Oncology, 2023)
Background and purpose: Pancreatic cancer (PC) is the fourth leading cause of cancer death in both men and women. The standard of care for patients with locally advanced PC of chemotherapy, stereotactic radiotherapy (RT) or chemo-radiation-therapy has shown highly variable and limited success rates. However, three-dimensional (3D) Pancreatic tumor organoids (PTOs) have shown promise to study tumor response to drugs, and emerging treatments under in vitro conditions. We investigated the potential for using 3D organoids to evaluate the precise radiation and drug dose responses of in vivo PC tumors. Methods: PTOs were created from mouse pancreatic tumor tissues, and their microenvironment was compared to that of in vivo tumors using immunohistochemical staining. The organoids and in vivo PC tumors were treated with fractionated X-ray RT, 3-bromopyruvate (3BP) anti-tumor drug, and with a combination of 3BP + fractionated RT. Results: Pancreatic tumor organoids (PTOs) exhibited a similar fibrotic microenvironment and molecular response (as seen by apoptosis biomarker expression) as in vivo tumors. Untreated tumor organoids and in vivo tumor both exhibited proliferative growth of 6 folds the original size after 10 days, whereas no growth was seen for organoids and in vivo tumors treated with 8 Gy of fractionated RT. Tumor organoids showed reduced growth rates of 3.2x and 1.8x when treated with 4 and 6 Gy fractionated RT, respectively. Interestingly, combination of 100 µM of 3BP + 4 Gy of RT showed pronounced growth inhibition as compared to 3-BP alone or 4 Gy of radiation alone. Further, positive identification of SOX2, SOX10 and TGF-β indicated presence of cancer stem cells in tumor organoids which might have some role in resistance to therapies in pancreatic cancer. Conclusions: PTOs produced a similar microenvironment and exhibited similar growth characteristics as in vivo tumors following treatment, indicating their potential for predicting in vivo tumor sensitivity and response to RT and combined chemo-RT treatments.